A New and Practical Method for Measuring Sponge Spicules - Rieuwpassa, Frets J.; Tomasoa, Aprelia M.; Palawe, Jaka F. P.; Rieuwpassa, Fredrik; Mege, Revolson Alexius; Balansa, Walter (Jurnal Ilmiah Platax, 2023)
Binocular light microscopy (BLM) is an excellent match for a scanning electron microscope (SEM) and a trinocular light microscope equipped with a micrometer (TLM). The practicality, user-friendliness, and short-time analysis of BLM make this method a good choice for spicule analysis. However, its effectiveness and accuracy are yet to be confirmed. This study aimed to validate the effectiveness of BLM by comparing its usefulness to both TLM and the gold standard methods. BLM was first subjected to measuring megascleres and microscleres of 2 sponges. Then, by using the If function built-in Excell and t-test in SPSS 16.0, the compatibility of BLM was evaluated against SEM by measuring the length of spicules from 4 Sangihe sponges and their counterpart species from different locations. Furthermore, the t-test analysis was used to validate the compatibility and effectiveness of our method to the TLM by measuring the spicules of four sponges. Both the F-function and the t-test analysis proved BLM was compatible with SEM with both measurements showing a perfect match for megascleres typed spicules of 4 compared sponges. This new technique also showed a perfect match with SEM (p = 0.367, t-test) and with TLM (p = 0.963, t-test). Keywords: Spicules, sponges, SEM, Wallacea, biomaterial, sponge taxonomy